Determinação de enxofre em amostras de grafite flexível por ICP OES utilizando piroidrólise como preparo de amostra - Nunes, Thieli Schaefer (2013)
The flexible graphite is a material produced from the intercalation, exfoliation and compression of graphite. Due to its low porosity, high chemical and thermal resistance, the flexible graphite is used in many different industries, including nuclear power plants. However, flexible graphite should be analyzed with respect to sulfur concentration, in order to evaluate residues of sulfur remaining from the intercalation process with sulfuric acid. The high chemical resistance of flexible graphite does not allow it to be easily decomposed using conventional methods of sample preparation using wet digestion in a closed system. In this sense, this work proposed a method employing pyrohydrolysis for sample preparation of flexible graphite and subsequent sulfur determination by optical emission spectrometry with inductively coupled plasma ( ICP OES ). Initially, several parameters which influence the volatilization of sulfur during piroidrólise, such as furnace temperature, pyrohydrolysis time, air flow rate and water absorbing solution, were investigated. Temperature of 1000 °C, pyrohydrolysis reaction time of 40 min, 0.5 mol L-1 H2O2 as absorbing solution, air and water flow of 0.1 and 0.5 L min-1 respectively, were used for flexible graphite decomposition and further determination of sulfur by ICP OES. Accuracy of the proposed method was evaluated using certified reference material of petroleum coke (NIST SRM 2718). Agreement better than 96% with certified values was obtained. Microwave-induced combustion (MIC) was used as a comparative method of sample digestion. Emission line of 180.669 nm was used for sulfur determination by ICP OES. Significant differences (student t-test, 95% confidence level) of sulfur results were not observed when pyrohydrolysis and MIC methods were compared. Limit of quantification of 54 μg g-1 was obtained using 100 mg of sample and a final volume of the absorbing solution equal to 30 mL. The proposed method was relatively simple and cheap. Low amount of reagents are necessary, which is in agreement with green chemistry recommendation.